This is an easy and basic derivative question.
k'(x) =((f(x))^-1)'
= -(f(x))^-2*f'(x)
so:
k'(2)= - (f(2))^-2 * f'(2)
=-4^-2 * (4.3-4)/(2.1-2)
= -9/16
This is an easy and basic derivative question.
k'(x) =((f(x))^-1)'
= -(f(x))^-2*f'(x)
so:
k'(2)= - (f(2))^-2 * f'(2)
=-4^-2 * (4.3-4)/(2.1-2)
= -9/16
WENXUECITY.COM does not represent or guarantee the truthfulness, accuracy, or reliability of any of communications posted by other users.
Copyright ©1998-2025 wenxuecity.com All rights reserved. Privacy Statement & Terms of Use & User Privacy Protection Policy